PENGARUH PENDAYAGUNAAN DANA INFAQ LAZNAS LMI SURABAYA TERHADAP KESEJAHTERAAN MUNFIQ LAHU - M.Jaenudin; Gunawan, Echa Valentina; Muljaningsih, Sri (Islamic Economics and finance in Focus, 2023)
This research discusses more deeply about infaq funds which one are one of the most donation posts in philanthropic institutions, especially the national amil zakat institution (Laznas). This study aims to analyze the effect of utilization, infaq funds on the welfare of munfiq lahu at Laznas LMI Surabaya area. This research uses a quantitative research method that refers to primary data, this study examines as many as 161 sample data using the Paired T-Test. Welfare theory in this research is translated into two variables, namely income variable and spiritual variable. The research findings show that the income variable affects the munfiq lahu’s welfare. The results of the study show that at Laznas LMI Surabaya area, the utilization of infaq funds distributed to munfiq lahu has an effect on income and spiritual variables with a note that internal parties Laznas LMI Surabaya area continue to provide assistance, montoring and periodic evaluation to munfiq lahu. This study shows that Laznas LMI Surabaya area is able to carry out to mandate from munfiq/donors to properly distribute infaq funds to munfiq lahu. Keywords: Utilization; Infaq Fund; Munfiq Lahu Welfare; Philanthropy Institute